Hybrid decision-making and optimisation framework for manufacturing-remanufacturing closed loop systems - Saleh Bagalagel; Waguih ElMaraghy (International Journal of Sustainable Engineering, 2021)
Remanufacturing of end-of-life products is one of the most preferred disposition alternatives to address environmental and economic concerns. In this paper, a hybrid decision-making framework is proposed to address the strategic planning issues of manufacturing-remanufacturing closed loop systems. The framework consists of qualitative and quantitative parts. The AHP-based qualitative part can be used to determine the configuration of the closed-loop network. The framework takes into consideration the product complexity and other characteristics as well as the supply chain network structure. The model considers the concerns of a manufacturer who offers a variety of complex modular products. The second part of the framework provides a quantitative optimisation model of technology implementation. A case study from the washing machine industry sector is used to illustrate the application of the proposed decision-making framework.